Issues Relating to Agricultural Markets and Trade Fairs Held in Timisoara - Ioana Anda Milin; Raul Gordean; Iuliana Ioana Merce; Tiberiu Iancu (Scientific Papers Animal Science and Biotechnologies, 2023)
Agricultural production has the following purposes-consumption, the supply of reserves (at household and national level), processing (via the traditional or industry), sales (on the market or through intermediaries) export. Mutations occurring in the Romanian rural market, trade in general, itself generated by commercial activity or customer. The paper examines issues related to trade issues held in the wholesale food markets and retail and inventory Timisoara main agricultural exhibitions held in Timisoara, Timis county and international participating farmers in the area. The paper covers issues related to the organization of trade in these markets - wholesale and retail, from a theoretical perspective and the effective deployment of sales in the markets Timis. Timisoara Municipality maintains a wholesale market and 10 retail food market with daily program in which sells various groups of traditional regional and international food. The fairs create the opportunity for farmers to be able to sell surplus agricultural products to and thus large revenues to ensure such restarting agricultural production process. The conclusions drawn from the analysis carried out,  have highlighted many positive aspects to the unfolding of trade through markets, food fairs and exhibitions in Timis county, but also issues related to the organization of trade and urban areas as a whole.